The Legal Effects of Contractual Imbalance Resulting from Hardship: An Analytical Study under Article 1195 of the Amended French Civil Code - Dalem, Raghad; Al-Saadi, Jalil (Journal of Legal Sciences, 2026)
Contracts, in general, must be executed in accordance with their provisions, obligating both parties to fulfill their commitments as stipulated. However, unforeseen circumstances may arise during the execution of a contract, rendering its performance burdensome and thereby affecting the contractual balance that existed at the time of its conclusion. Generally, legal systems include provisions within their civil laws to address such burdens and the resulting economic imbalance. While the principles addressing these situations are consistent across laws, the differences lie in the remedies and means of restoring economic balance, whether through modification or termination. Article 1195 of the amended French Civil Code establishes a rule for unforeseen and extraordinary circumstances causing hardship to one of the contracting parties. This provision moves away from the partial solutions previously offered by the French Court of Cassation in its various rulings and ends the legal uncertainty among scholars regarding the impact of unforeseen circumstances. It also bridges the gap between French law and its counterparts concerning the recognition of the theory of hardship.